A checklist of the parasitic helminths of cricetid and heteromyid rodents in Mexico - Preisser, Whitney C; Falcón-Ordaz, Jorge (THERYA, 2019)
Abstract We present an updated checklist of helminth species infecting cricetid and heteromyid rodents (Rodentia: Cricetidae and Heteromyidae) distributed in Mexico. For each helminth record, we include information on helminth taxonomy, location within the host, life stage, host associations, collection localities, citation, and museum collections, when available. We recorded more than 73 helminth species from 47 host species distributed across 21 states in Mexico. The present list represents the most up-to-date knowledge of helminth species infecting cricetid and heteromyid rodents in Mexico.